Calculation and application of eddy dissipation rate map based on spectrum width data of a S-band radar in Hong Kong (MAUSAM, 2016)
The spectrum width data of an S-band radar in Hong Kong are used to calculate the map of eddy dissipation rate (EDR) with the objective of providing turbulence alerting service for the en-route aircraft in the Pearl River Delta region.  The calculation methodology is different from that reported in the existing literature by also removing the wind shear contribution in determining the radar-based EDR.  The performance of the EDR maps obtained from the conical scans of the radar is illustrated in two examples of moderate to severe turbulence reported by the aircraft.  In both cases, based on the EDR values and windshear hazard factors determined from the aircraft data, the airflow disturbances could adversely affect the operation of the aircraft.  By overlaying the flight route on the radar’s reflectivity imageries, it appears that, in both cases, the disturbed airflow is associated with rather intense rain cells, though they are rather small and isolated.  The EDR values calculated from the radar’s spectrum width data at the locations of the rain cells are generally consistent with those determined using the aircraft’s wind measurements.  From the selected cases, it seems that the radar-based EDR values have generally satisfactory quality.  If such data could be available at the cockpit through data uplinking, they could be useful hints for the pilots not to fly through the rain cells but rather going around them.  The methodology may be applied to the radars in the Pearl River Delta region in order to construct a three-dimensional mosaic of turbulence intensity for the assurance of aviation safety.